‘Mil rochas e tal...!’ : inventário dos sítios da arte rupestre do Vale do Côa (conclusão) - Reis, Mário (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Since its discovery, the rock art of the Côa region has not ceased to increase its numbers, which are reflected at this point in more than 80 sites, with a quantity of engraved rocks that quite exceeds one thousand records. In the first and second parts of this paper we presented a description of the sites scattered along the two main axes of the rock art distribution, the rivers Côa and Douro, respectively. In this third and last part we present an inventory update and the final conclusions, with a review on the knowledge obtained on each of the four chronological periods of the Côa rock art, and also an addendum with the new inventory data obtained in the meantime.